Whey protein hydrolysates enhance grapevine resilience to abiotic and biotic stresses - Alfonso, Esteban; Andlauer, Wilfried; Brück, Wolfram Manuel; Rienth, Markus (Frontiers in Plant Science, 2025)
IntroductionThe growing need for sustainable viticulture has increased interest in biostimulants that enhance plant resilience to abiotic and biotic stresses. This study evaluates the efficacy of whey-derived protein hydrolysates (PHs) in improving Vitis vinifera cv. Cabernet Sauvignon tolerance to combined heat and drought stress and reducing pathogen infections.MethodsPotted grapevines were subjected to 40°C heat stress without irrigation and treated with either water or PHs. Physiological parameters as well as key stress- and photosynthesis-related genes expression were monitored. The antimicrobial effects of PHs against Plasmopara viticola and Botrytis cinerea were also assessed.ResultsPHs-treated plants exhibited a faster recovery of photosynthetic activity than control plants and maintained normal sub-stomatal CO2 concentrations under combined abiotic stress. PHs treatment significantly upregulated heat stress-responsive genes (HSFA2, HSP101) and mitigated the stress-induced decline in photosynthesis-related genes (LHCA3, RbcS). Moreover, PHs significantly enhanced grapevine drought tolerance, as indicated by higher leaf water potential values and expression of drought-responsive genes (NCED1, TIP2;1). Additionally, PHs demonstrated a direct toxic effect on P. viticola, inhibiting zoospore germination and reducing sporulation on leaf discs, while reducing B. cinerea infection in berries when applied post-infection.ConclusionIn the tested conditions, whey PHs serve as effective biostimulants, enhancing grapevine resilience to combined drought and heat stress while providing protection against grapevine pathogens. Although further validation in vineyard conditions is needed, this dual benefit of PHs may propose a potential sustainable alternative to reduce chemical inputs in viticulture, contributing to more environmentally friendly agricultural practices.